2013
DOI: 10.1186/2193-9039-2-5
|View full text |Cite
|
Sign up to set email alerts
|

The productivity of return migrants: the case of China’s “Sea Turtles”

Abstract: This paper explores the productivity differential between return migrants ("Sea Turtles") and non-migrants through a case study of China's venture capital (VC) industry. I find that even after correcting for selection bias, return venture capitalists are less productive than comparable non-migrants in targeting promising projects and/or providing value-added services. Given that the VC industry is a useful laboratory in which to look at the performance of return migrants and China's economic development, I dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
(39 reference statements)
1
16
0
Order By: Relevance
“…In contrast, my results do not suggest that accounting and engineering skills acquired in Singapore and Malaysia are favored by employers in Myanmar, with the possible explanation being that accounting and engineering practices tend to be country-or local-specific. My findings seem to be in line with prior findings indicating that some skills acquired overseas are less transferrable to a local labor market and, thus, do not always translate into improved productivity (e.g., Sun 2013).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, my results do not suggest that accounting and engineering skills acquired in Singapore and Malaysia are favored by employers in Myanmar, with the possible explanation being that accounting and engineering practices tend to be country-or local-specific. My findings seem to be in line with prior findings indicating that some skills acquired overseas are less transferrable to a local labor market and, thus, do not always translate into improved productivity (e.g., Sun 2013).…”
Section: Discussionsupporting
confidence: 81%
“…In this study, I analyze the employment outcomes of returnees, which has received little attention in the extant literature. Despite prior studies showing that returnees are more likely to earn higher wages than non-migrants (Wahba 2015;Reinhold and Thom 2013;Co et al 2000;Barrett and Goggin 2010;Martin and Radu 2012), a host of factors including a lack of characteristics crucial for finding employment and performing well on a job in local context (e.g., social ties and connections) and a mismatch of skills could inhibit their full participation in local labor markets (Sun 2013;Martin and Radu 2012). Overall, I find limited impact of foreign work experience on employment outcomes in the Myanmar labor market.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…5 An important question which has attracted limited attention is: what are the returns to overseas work experience? Although there is a handful of studies which have looked at the returns to returning migrants by examining the wage premium of return migrants compared to non-migrants, for example Co, Gang and Yun (2000), Barrett and O'Connell (2001), Goggin (2010), andDe Coulon andPiracha (2005), focusing on transitional economies or developed countries 4 See also Docquier and Rapoport (2012) for a survey of the brain drain and brain gain literature 5 Sun (2013) examines the productivity difference between domestic venture capitalists and their foreign educated counterparts in China.…”
Section: Previous Literaturementioning
confidence: 99%
“…For example, Gibson et al (2010 and2013) took advantage of a randomized lottery in the choice of migrants to New Zealand. Comparing the incomes of Tongan migrants to those who applied to migrate to New Zealand but whose names were not drawn in the ballot, Gibson et al (2010) found evidence of positive selection.…”
Section: Introductionmentioning
confidence: 99%